The Fps/Fes kinase regulates leucocyte recruitment and extravasation during inflammation - Parsons, Sean A (Blackwell Science Inc, 2007)
Fps/Fes and Fer comprise a distinct subfamily of cytoplasmic protein-tyrosine kinases, and have both been implicated in the regulation of innate immunity. Previous studies showed that Fps/Fes-knockout mice were hypersensitive to systemic lipopolysaccharide (LPS) challenge, and Fer-deficient mice displayed enhanced recruitment of leucocytes in response to localized LPS challenge. We show here for the first time, a role for Fps in the regulation of leucocyte recruitment to areas of inflammation. Using the cremaster muscle intravital microscopy model, we observed increased leucocyte adherence to venules, and increased rates and degrees of transendothelial migration in Fps/Fes-knockout mice relative to wild-type animals subsequent to localized LPS challenge. There was also a decreased vessel wall shear rate in the post-capillary venules of LPS-challenged Fps/Fes-knockout mice, and an increase in neutrophil migration into the peritoneal cavity subsequent to thioglycollate challenge. Using flow cytometry to quantify the expression of surface molecules, we observed prolonged expression of the selectin ligand PSGL-1 on peripheral blood neutrophils from Fps/Fes-knockout mice stimulated ex vivo with LPS. These observations provide important insights into the observed in vivo behaviour of leucocytes in LPS-challenged Fps/Fes-knockout mice and provide evidence that the Fps/Fes kinase plays an important role in the innate immune response.